Performance Predictors in Elite Athletes: Evaluating the Role of Eccentric Utilization Ratio and Mechanical Power Outputs - Selman Kaya; Mehmet Ersöz (Applied Sciences, 2025)
This study aimed to examine the relationship between the eccentric utilization ratio (EUR) and sprint, change of direction (COD), change of direction deficit (CODD%), and vertical jump performance, including countermovement jump (CMJ) and squat jump (SJ). A total of 32 elite athletes (16 women and 16 men) participated. Performance was evaluated using force platforms and photocell timing systems during CMJ, SJ, 30 m sprint, and Pro-Agility tests. Pearson correlation and simple linear regression analyses were used to assess the relationships between EUR and performance variables. The results revealed that EUR was significantly associated with CMJ height (r = 0.587, p = 0.017) and 0–10 m sprint performance (r = 0.516, p = 0.041) in female athletes, whereas no significant relationships were found in males (r < 0.20, p > 0.05) for all performance variables. In contrast, strength–power metrics such as eccentric peak power (ECCPP), eccentric mean power (ECCMP), concentric mean power (CONMP), and peak power (PP) showed stronger associations with all performance variables, including COD, sprint segments, and jump tests. In conclusion, although EUR demonstrated limited predictive value particularly in male athletes directly measured strength–power variables appear to be more reliable indicators of athletic performance. These findings highlight the importance of prioritizing eccentric and concentric power outputs in performance assessment and individualized training strategies.